Unveiling the Prognostic Power of HRR in ICU-Admitted COPD Patients: A MIMIC-IV Database Study - Wang Y; Chen D; Zhang C; Yang H (International Journal of COPD)
Yuan Wang,1 Dan Chen,2 Chunlu Zhang,3 Haiying Yang1 1Department of Respiratory and Critical Care Medicine, The Second People’s Hospital of Meishan City, Meishan, Sichuan, 620500, People’s Republic of China; 2Department of Respiratory Medicine, Yunchang Hospital, Meishan, Sichuan, 620500, People’s Republic of China; 3Department of Geriatrics, Chengdu Sixth People’s Hospital, Chengdu, Sichuan, 610051, People’s Republic of ChinaCorrespondence: Yuan Wang, Department of Respiratory and Critical Care Medicine, The Second People’s Hospital of Meishan City, Meishan, Sichuan, 620500, People’s Republic of China, Email 2693855887@qq.comObjective: This study sought to examine the potential relationship between Hemoglobin/Red Cell Distribution Width Ratio (HRR) and the all-cause mortality risk in critically ill patients with chronic obstructive pulmonary disease (COPD).Patients and Methods: In a retrospective analysis of the MIMIC-IV database, patients were divided into two groups based on a specific HRR threshold. Propensity score matching (PSM) was employed to address covariate imbalances. Logistic regression models was used to examine the association between HRR and mortality. A restricted cubic spline (RCS) model was employed to visualize the association between HRR and mortality. Receiver Operating Characteristic (ROC) curves were utilized to assess the predictive capability of HRR, and Decision Curve Analysis (DCA) was conducted for clinical evaluation. Furthermore, subgroup analyses were performed to explore potential variations within specific cohorts.Results: A comprehensive analysis identified a total of 1,061 patients. The threshold value established for HRR is 5.395 g/L/%. Following the application of PSM, the matched cohort comprised 544 patients. Both the original and matched cohorts exhibited higher rates of all-cause mortality and extended hospital stays among individuals with low HRRs. Logistic regression analyses demonstrated that HRR is an independent risk factor of mortality. The RCS analysis demonstrated a significant linear relationship between HRR and mortality. The ROC curves yielded values of 0.58 for the original cohort and 0.60 for the matched cohort. DCA analysis indicated that HRR is clinically valuable. Subgroup analyses further validated the robustness of these core findings.Conclusion: A lower HRR is positively associated with all-cause mortality in critically ill patients with COPD.Keywords: COPD, red blood cell distribution width, hemoglobin, all-cause hospital mortality, MIMIC-IV